2012
DOI: 10.1111/j.1468-0416.2012.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical and Empirical Review of the EU Regulation on Credit Rating Agencies: In Search of Truth, Not Scapegoats

Abstract: The undergoing financial turbulence has raised significant concerns over the role that credit rating agencies (CRAs) played in the inception, magnification and expansion of the crisis. In response, the EU legislature has adopted Regulation 1060/2009, which, for the first time, set out a legally binding pan‐European authorization regime for CRAs, which issue ratings that have been used by EU‐based financial institutions. As the turmoil turned into an unprecedented Eurozone debt crisis, EU politicians have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 189 publications
(270 reference statements)
0
9
0
Order By: Relevance
“…While the revisions may denote a changing regulatory climate, it could be surmised that they were not well-thought through, hence the rapid revisions. Since their inception in 2009 concerns have been raised that the regulations were not finely-tuned enough to address the problems that had led to the crisis in the first place (Staikouras, 2012); that they were not adequate to address the legacy problems in the industry (Papaikonomou, 2010;Utzig, 2010) and that they had unintended consequences on the market (Avgouleas, 2010). This study therefore sought to gauge market participants' perceptions of the EC regulations to investigate the above concerns.…”
Section: Lack Of Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…While the revisions may denote a changing regulatory climate, it could be surmised that they were not well-thought through, hence the rapid revisions. Since their inception in 2009 concerns have been raised that the regulations were not finely-tuned enough to address the problems that had led to the crisis in the first place (Staikouras, 2012); that they were not adequate to address the legacy problems in the industry (Papaikonomou, 2010;Utzig, 2010) and that they had unintended consequences on the market (Avgouleas, 2010). This study therefore sought to gauge market participants' perceptions of the EC regulations to investigate the above concerns.…”
Section: Lack Of Transparencymentioning
confidence: 99%
“…The securities industry has for a long time operated without regulation, triggering incessant calls for regulation, particularly the regulation of CRAs. Despite the gazetting of the 2009 EC regulations, various scholars raised concerns that the regulations were not finely-tuned enough to address the problems that had led to the crisis in the first place (Staikouras, 2012); that they were not an adequate (Nichols et al, 2011;Papaikonomou, 2010;Utzig, 2010) and that they posed unintended consequences (Avgouleas, 2010)as they were not well-thought through (Fisch, 2010). Using a selection of metaphors drawn from participants in this study, results indicated a pervasive concern by UK-based study participants, echoing evidence from extant literature.…”
Section: Conclusion Implications and Further Researchmentioning
confidence: 99%
“…This strategic position in the new 815 global political economy has afforded them increased influence over the movements of private capital. This influence is further reinforced by the use of the agencies' output in official regulatory schemes in the U.S and elsewhere (cf., Bruner and Abdelal, 2005;Staikouras, 2012). Therefore, CRAs are promoted to gatekeepers of substantial amounts of capital, and access to these investment sources often relies on rating scores.…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…This question represents one of the most contentious issues of the ongoing debate at the international level. However, there is a lack of a detailed and coherent picture that is able to synthesize the different perspectives of analysis to provide answers to the open questions regarding the need for regulation (Dittrich 2007;Staikouras 2012). Therefore, this article investigates the changes regarding the role and regulation of CRAs in theory and practice, focusing on the European Union.…”
Section: Introductionmentioning
confidence: 99%